Salvageable waste associated with intravitreal injections: A local medical waste management approach. (16th November 2022) - Rogerson, Thomas; Dedina, Liana; Goggin, Michael; Chan, Weng Onn
Abstract: Background: Healthcare waste management is a globally challenging issue with an increased prevalence of disposable, single‐use materials in developed countries and a rapidly ageing population continuing to drive an increase in the use of medical resources. One manifestation of this within ophthalmology is the increasing number of intravitreal injections given for conditions such as age‐related macular degeneration and diabetic macular oedema. Methods: A prospective controlled cohort study was performed over 5 weeks in 2021 during which two sites were selected to compare different approaches to sorting the waste generated by intravitreal injections. At Site A all waste associated with these injections was placed in standard hospital waste bins. Site B was the intervention arm where a real‐time sorting of waste occurred. The number of injections given and waste amounts were recorded. Results: 116 and 286 injections were given at Sites A and B, respectively over the study period. Site A generated an average of 470.7 g of waste per injection compared with 175.1 g at our intervention site. This represents a 62.8% reduction ( p < 0.001). At Site B, where waste was sorted, a total of 50.1 kg of medical waste was generated from these injections during the study period of which 33.8 kg (67.5%) was salvageable. Conclusions: This is the first quantification of the medical waste associated with intravitreal injections, a burgeoning treatment for macular degeneration and diabetic retinopathy among other conditions. This study demonstrates a significant reduction in the amount of medical waste produced using an easily implementable real‐world methodology.